Antioxidant, antimicrobial and cytotoxic potential of condensed tannins from Leucaena leucocephala hybrid-Rendang - Mazni Abu Zarin; Ho Yin Wan; Azizul Isha; Nurdin Armania (Food Science and Human Wellness)
Condensed tannins (CTs) are one of the promising compounds due to their potentially health-promoting qualities. In this study, CTs were extracted from a Leucaena leucocephala hybrid-Rendang and subjected to various biological studies including antioxidant (using Ferric reducing antioxidant power (FRAP), DPPH and ABTS radical scavenging assay), anti-microbial (against different pathogens) and cytotoxic activities (toward human breast adenocarcinoma (MCF-7), human colon carcinoma (HT29), human cervical carcinoma (HeLa) and human liver carcinoma (HepG2) cell lines) in cancer cells through in vitro experiments. The structural characteristics and purity of CTs extract were determined using 13C NMR. The results showed that CTs exhibited higher in vitro antioxidant activities (2257.12 ± 80.55 mg TEAC/g extract, 605.3 ± 1.82 mg TEAC/g extract and 1014.03 ± 1.20 mg TEAC/g extract in FRAP, ABTS and DPPH assay, respectively) and demonstrated anti-microbial activities toward selected Gram's positive and Gram's negative bacteria tested with MIC and MBC value at 6.25–50 mg/mL. Furthermore, among other selected cancer cells, CTs also demonstrated cytotoxic activity toward human breast cancer cells (MCF-7) (IC50 = 38.33 ± 2.08 μg/mL). Characteristic of apoptosis such as cell shrinkage, nuclear condensation and apoptotic bodies were shown in MCF-7. These preliminary investigations have provided scientific rationale to use CTs as an alternative therapy for various oxidative and inflammatory associated diseases.